Professional Development in Digital Loop: Impact of ICT on Mathematics Teachers’ Self-Efficacy and Practice - Dahal, Prem Prasad (Mangal Research Journal, 2025)
mathematics education has transformed teaching practices and reshaped models of teacher professional development (TPD). This systematic review examines the effects of ICT-based TPD on mathematics teachers’ self-efficacy, technological pedagogical content knowledge (TPACK), and instructional practices, while identifying effective program features that foster digital competence and pedagogical innovation. This review analyzed thirty peer-reviewed studies published between 2018 and 2025 following the PRISMA framework, drawing data from Scopus, Web of Science, ERIC, SpringerLink, and ScienceDirect. Interventions included blended learning, GeoGebra-based training, MOOCs, and simulation-supported modeling. The findings reveal that ICT-integrated TPD enhances teachers’ confidence, digital competence, and instructional creativity—especially when programs emphasize active learning, sustained mentoring, and collaborative professional communities. Persistent challenges remain, such as limited infrastructure, institutional barriers, and the digital divide that restrict large-scale implementation. Overall, the review underscores the need for context-responsive, scalable professional learning frameworks that balance technology, pedagogy, and content knowledge to advance mathematics teaching and learning in the digital age.